Multi organ assessment of compensated cirrhosis patients using quantitative magnetic resonance imaging - Bradley, Christopher R.; Cox, Eleanor F.; Scott, Robert A.; James, Martin W.; Kaye, Philip; Aithal, Guruprasad P.; Francis, Susan T.; Guha, Indra Neil (Elsevier, 2018)
Background and Aims: Advancing liver disease results in deleterious changes in a number of critical organs. The ability to measure structure, blood flow and tissue perfusion within multiple organs in a single scan has implications for determining the balance of benefit versus harm for therapies. Our aim was to establish the feasibility of Magnetic Resonance Imaging to assess changes in compensated cirrhosis (CC), and relate this to disease severity and future liver related outcomes (LROs). Methods: 60 CC patients, 40 healthy volunteers and 7 decompensated cirrhotics were recruited. In a single scan session, MRI measures comprised phase-contrast MRI vessel blood flow, arterial spin labelling tissue perfusion, T1 longitudinal relaxation time and volume assessment of liver, spleen and kidneys, heart rate and cardiac index. We explore MRI parameters with disease severity and differences in baseline MRI parameters in those 11 (18%) of CC patients who had future LROs. Results: In the liver compositional changes were reflected by increased T1 in progressive disease (p<0.001) and an increase in liver volume in CC (p=0.006), with associated progressive reduction in liver (p < 0.001) and splenic (p<0.001) perfusion. A significant reduction in renal cortex T1 and increase in cardiac index and superior mesenteric arterial (SMA) blood flow was seen with increasing disease severity. Baseline liver T1 (p=0.01) and perfusion (p< 0.01), and renal cortex T1 (p<0.01) were significantly different in CC patients who subsequently developed negative LROs. Conclusions: MRI allows the contemporaneous assessment of organs in liver cirrhosis in a single scan without the requirement of contrast agent. MRI parameters of liver T1, renal T1, hepatic and splenic perfusion, and SMA blood flow were related to risk of LROs.